Soils and the environment an introduction - Wild, Alan (Cambridge University Press, 1993)
Soil is one of humankind's most important resources, providing for the growth of arable crops, grassland and trees, which give us food, fibre, and timber. As part of the natural environment, soil supports the plant growth needed for the cycling of gases, provides a habitat for a wide range of organisms, buffers the flow of water and solutes between the atmosphere and ground and surface waters, and acts as both a source and sink for gases in the atmosphere. This introductory text aims to help students understand the behaviour of soils in both the man-made and the natural environment. The book is structured in two parts: Part A is an introduction to general soil properties and processes, whilst Part B considers soil in relation to the environment, covering topics such as the role of soil in supporting plant growth, in maintaining a clean environment, and in the flux of atmospheric gases. Issues such as acidification, contamination, conservation and erosion are also considered